A punição como reconciliação em Hegel - de Vasconcelos Costa, Daniel (Revista Eletrônica Estudos Hegelianos, 2019)
In this article, I focus on Hegel’s approach on the problem of punishment. I argue that the traditional, or orthodox, interpretation of Hegel’s penal theory that sees it as a retributive approach is wrong. This mistake resides on the lack of knowledge about the possible categories about the function of the penal law as well as how we could conceive punishment. I try to solve this problem through the contemporary penal law theories, in special, German penal law theories, which present us new concepts that allow us to distinguish different structures of the penal law system, and so, different questions about it. In the end, it will be possible to comprehend how Hegel proposed a penal law theory that rather than being retributive was an approach known today as the unified theory of positive general prevention of the function of penal law, where the punishment had an expressive function connected with the demands of justice.